Recent advances on photocatalytic geopolymer on the degradation of organic pollutants: A review - Yaacob, Noorulayuni Atiqah; Abdullah, Mohd Mustafa Al Bakri; Ming, Liew Yun; Ishak, Shafiq; Vizureanu, Petrica; Tanyildizi, Harun; Mohamed, Rosnita (Elsevier, 2026)
The widespread occurrence of organic pollutants, particularly antibiotic and dye residues, in both aquatic and terrestrial ecosystems pose a significant environmental threat and contributes to the concerning increase in human health risks. Often, these persistent contaminants are not eliminated by conventional water treatment methods. Thus, the effective management of organic pollutants in water is indeed a complex and ongoing issue, requiring significant attention from academic researchers. Indeed, geopolymer-based photocatalysts have gained popularity as a promising and eco-friendly approach for the treatment of organic pollutants in water in recent years. However, despite the growing interest, literature details on the application of geopolymer in photo-degradation of organic pollutants is insufficient. Therefore, this review highlights the recent advancements in the development of geopolymer-based photocatalysts on organic pollutants degradation and the geopolymerization process. In addition, the operational parameters influencing photocatalytic degradation such as effect of pH, catalyst dosage, and initial concentration of pollutants are briefly reviewed to highlight the significance of the parameters that critically impacted the photocatalytic degradation efficiency. The fundamental mechanism of organic pollutants, recent advances, and practical application of photocatalytic degradation are also discussed. This would aid in setting the trajectory for providing references on efficient geopolymer-based photocatalysts, establishing new insights and potential applications for effective wastewater remediation.
Keywords: Organic pollutants; Photocatalytic degradation; Geopolymer; Wastewater